Peran Orang Tua Dalam Membentuk Karakter Anak Usia 5-6 Tahun Di Desa Bumi Restu - Nadela Sustiarini; Nihwan (Ash-Shobiy: Jurnal Pendidikan Islam Anak Usia Dini dan Al-Qur'an, 2023)
Early childhood spends most of their time in the family, which is the first and foremost place for children to get education, the lack of politeness of a child to adults by using bad language (swearing) and often occurs in early childhood badmouthing friends peers at school and in the neighborhood. This research method is descriptive qualitative. The research subjects were parents who had children aged 5-6 years. Data collection techniques observe and record the things that are needed. Data analysis techniques use data reduction, data display, and drawing conclusions. Based on research conducted by researchers in the field regarding the role of parents in shaping the character of children aged 5-6 years in Bumi Restu Village, obtained from the results of interviews and observations conducted by researchers a. Educating Through Example of Behavior b. Implementing Early Education System c. Culture of Dialogue Between Parents and Children d. Apply the Principle of Fairness in Managing Available Time.